Le crime organisé et la guerre aux stupéfiants : crise et réforme - Mitchell, Chet (Criminologie, 1989)
War is a form of competition and the drug wars are no exception to this definition. Drug wars are actually classic illustrations of competitors abusing the legal process to define their own drug trading as lawful while characterizing their competitor's behaviour as “crime”. Successive American federal administrations extended the drug wars through a combination of military assistance, financial pressure and secret agreements. These aggressions are the real abuses aimed at third world cultures. Since Americans purchase 60% of all illicit drugs and finance more than 90% of the police action against the trade, drug legalization drug crusade. On the other hand, even if drug legalization makes sense the U.S. federal government will not necessarily act sensibly. An alternative possibility is reform outside the U.S. capable of generating a competitive crises internationaly.